2005
DOI: 10.1149/1.1972319
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Luminescence Properties of Gd[sub 2]O[sub 3]:Eu[sup 3+] and Y[sub 3]Al[sub 5]O[sub 12]:Ce[sup 3+] Phosphor Particles Synthesized via Aerosol

Abstract: Opportunities for the synthesis of ultrafine spherical particles with uniformly distributed components and phases are of special importance when materials for photonic application are considered. In this study, the nanophase, spherical, luminescent polycrystalline Gd 2 O 3 :Eu and YAG:Ce particles were synthesized from aerosols of the corresponding nitrate solutions ultrasonically generated with frequencies of 1.7 MHz and 800 kHz, respectively. Detailed phase and structural analysis, compositional homogeneity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
0
50
1
Order By: Relevance
“…In all the samples maximum intensity peak is at 611 nm wavelength belonging to 5 D 0 ? 7 F 2 transition [20]. All observed transitions are due to the Eu 3+ in C2 and S6 crystallographic sites.…”
Section: Introductionmentioning
confidence: 84%
“…In all the samples maximum intensity peak is at 611 nm wavelength belonging to 5 D 0 ? 7 F 2 transition [20]. All observed transitions are due to the Eu 3+ in C2 and S6 crystallographic sites.…”
Section: Introductionmentioning
confidence: 84%
“…Yttrium oxide posses a cubic crystal structure with a space group, S.G. Ia3-(T 7 h ) in which there are two crystallographically different rare-earth sites, C2 (75%) and S6 (25%); by that, a unit cell is composed of four atom positions, three having a point symmetry C2 and one position with a point symmetry S6 [7]. ters in the host matrix and the overall particle structure and morphology control, which altogether signify the importance of innovative and controllable UCP phosphor processing route in the current research efforts [7][8][9]. Moreover, of particular impor-tance is the controlled synthesis of the host lattice having targeting crystal structure which determines the distance between the dop-ant ions, their relative spatial position, their coordination numbers, and the type of anions surrounding the dopant.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, hot wall aerosol route has been recognized as successfull to obtain submicronic Eu 3+ -doped nanocrystalline down-conversion Y 2 O 3 , (Y 1Àx Gd x ) 2 O 3 and Gd 2 O 3 phosphor particles with advanced structural, morphological and luminescent properties [8,9,16]. It has been demonstrated that the key particle formation parameters are the physico-chemical properties of precursor solution, the manner of aerosol generation and the process parameters like temperature, residence time, and atmosphere determining the mechanisms of aerosol formation, solute precipitation, nucleation, growth and primary nanoparticles aggregation into a spherical assemblage [7].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] SP involves extreme synthesis conditions occurring at the level of a micrometer-sized aerosol droplet in a disperse system, thus enabling the synthesis of metastable structures, as previously reported. [21,22] There are certain process parameters, such as high heating and cooling rates, short residence times, and an additional thermal treatment, which may affect the yield of either thermodynamically (YAG, YAM) or kinetically (YAP) stable phases.…”
Section: Introductionmentioning
confidence: 99%